Improvement of the Conditioning Process to Enhance the Quality of Vanilla (Vanilla planifolia) - Andi Ulfa Hardianty Syahrullah; I Wayan Budiastra; Sutrisno Mardjan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The quality of national vanilla still does not fully meet national and international standards, one reason is the suboptimal conditioning process, namely, the final storage stage to stabilize quality. This study aims to examine the effect of packaging type, combined with temperature and conditioning duration, on vanilla's physical, chemical, sensory, and microbiological quality, and determine the best treatment combination in producing vanilla quality that meets SNI. Factorial Completely Randomized Design (CRD) was used in this experiment with three factors namely different material packaging (wax paper and HDPE plastic), various temperatures storage (25 °C, 30 °C, 35 °C), and conditioning durations (1, 1.5, and 2 months). Results showed that temperature, type of packaging, and conditioning duration significantly affect most of the physical, chemical, and microbiological quality parameters of vanilla, except for ash content and organoleptic aroma, which are not significantly different. The best treatment combination was obtained using HDPE packaging with a temperature of 35 °C for 1.5 months of conditioning, producing quality according to SNI 01-0010-2002 with high vanillin content and stable color. However, the total microbial count (TPC) in this treatment still exceeded the limits set by FAO.